HUBUNGAN ANTARA IMOBILITAS DAN STATUS FUNGSI MENTAL DENGAN TINGKAT KEMANDIRIAN LANSIA DI RW 013 KELURAHAN SUKATANI KECAMATAN TAPOS KOTA DEPOK JAWA BARAT - Aisyiah Aisyiah; Retno Widowati; Aditya Kurniawan (Jurnal Ilmu dan Budaya, 2017)
Elderly is an event that will surely be experienced by all people who have long life, and can not be avoided by anyone, but humans can attempt to inhibit the incident. To be able to live independently, the elderly must be able to adjust to the changes that occur. The purpose of this study is to determine the relationship between immobility and mental function status with the level of independence in the elderly in RW 013 Sukatani Village Tapos District Depok City West Java Province in 2016. The research used is an analytical method using cross sectional approach. The result of the research analysis found there is a significant correlation between immobility (p value = 0,000) and mental function status (p value = 0,000) with independence level in elderly in RW 013 Sukatani Village, Tapos Subdistrict, Depok City, West Java Province 2016. Therefore, the importance of the role of health workers working with families and the elderly themselves in preventing immobility in the elderly and improving the status of healthy mental functioning. This will affect the achievement of the level of independence of the elderly who will affect the improvement of Quality Of Life (QOL) elderly.